Astrocytic phagocytosis is a compensatory mechanism for microglial dysfunction. (22nd September 2020) - Konishi, Hiroyuki; Okamoto, Takayuki; Hara, Yuichiro; Komine, Okiru; Tamada, Hiromi; Maeda, Mitsuyo; Osako, Fumika; Kobayashi, Masaaki; Nishiyama, Akira; Kataoka, Yosky; Takai, Toshiyuki; Udagawa, Nobuyuki; et al.
Abstract: Microglia are the principal phagocytes that clear cell debris in the central nervous system (CNS). This raises the question, which cells remove cell debris when microglial phagocytic activity is impaired. We addressed this question using Siglech dtr mice, which enable highly specific ablation of microglia. Non‐microglial mononuclear phagocytes, such as CNS‐associated macrophages and circulating inflammatory monocytes, did not clear microglial debris. Instead, astrocytes were activated, exhibited a pro‐inflammatory gene expression profile, and extended their processes to engulf microglial debris. This astrocytic phagocytosis was also observed in Irf8 ‐deficient mice, in which microglia were present but dysfunctional. RNA‐seq demonstrated that even in a healthy CNS, astrocytes express TAM phagocytic receptors, which were the main astrocytic phagocytic receptors for cell debris in the above experiments, indicating that astrocytes stand by in case of microglial impairment. This compensatory mechanism may be important for the maintenance or prolongation of a healthy CNS. Synopsis: Microglial ablation or microglial dysfunction actuates phagocytic activity of astrocytes. Astrocytes possess phagocytic machinery and have the potential to compensate for microglia with dysfunctional phagocytic activity. Even in a healthy central nervous system, astrocytes possess phagocytic machinery, such as phagocytic receptors, Axl and Mertk. After microglia‐specific ablation, activated astrocytes, rather than non‐microglial mononuclear phagocytes, engulf microglial debris. Astrocytes phagocytose spontaneous apoptotic cells in Irf8‐deficient mice, in which microglia are present but dysfunctional. Abstract : Clearance of brain cell debris in the absence of functional microglia is not taken over by canonical phagocytic cell types, but surprisingly by astrocytes expressing TAM phagocytic receptors.